Exploring the impact of key physicochemical properties of rice on taste quality and instant rice processing - Yang, Wen; Li, Xiaoling; Zheng, Xiaohang; Wang, Mengyuan; Pan, Wenxu; Liu, Pin; Zhang, Zehua; Gong, Caixiong; Zheng, Ling; Yuan, Hua; Li, Ting; Chen, Weilan; et al. (Frontiers in Plant Science, 2024)
Taste quality is a fundamental criterion in assessing the overall of rice. However, there has been a lack of systematic studies investigating the impact factors of taste quality. In this study, chromosomal segment substitution lines (CSSLs) with notable differences in physicochemical properties were obtained by screening the CSSL population. A correlation analysis between the physicochemical properties and the taste qualities of rice revealed that amylose and protein content are significantly negatively correlated with the taste value of both freshly cooked and rehydrated instant rice. The Alkali spreading value(ASV) had limited impact on the taste value of rice, but low ASV rice is more resistant to cooking. Grain chalkiness played a critical role in maintaining the integrity of freshly cooked rice and instant rice grains after rehydration. In summary, our study provides crucial insights and guidance for rice breeding, with the goal of developing excellent quality and enhancing the processing of instant rice.